Women and biographical speech: subjectivity and authority - Esten, Antonia (Curtin University, 1998)
The thesis is concerned with the construction of women's authority as it is manifested in biographical speech; that is, in written or oral narratives, or sub-narratives, about others. The emphasis is on women's biography but certain other genres (notably gossip and the biographical research interview) are also examined.The central premise is that women as patriarchal subordinates are significantly disadvantaged in the cultural processes that construct (public) authority; also, that speaking about (defining) both ourselves and others is a significant means by which we construct knowledges - an important basis for authority. Women's collusion with patriarchal structures and processes, whether this be conscious or unconscious, creates problems with the construction of their authority on numerous levels in public and private domains. Moreover, even when women intend to operate subversively from sites of resistance, and when they succeed in doing so to some extent, the workings of power through discourse often render the overall effect of subversion to be consistent with, and ultimately supportive of, dominant ideology.The thesis examines a variety of aspects of these complex dynamics as they apply to women in the context of contemporary western societies. To this end, the first and last chapters consider women's relations to formal biography with the aim of identifying their (historic) engagement with lifestorying. Two chapters discuss the psychological/ideological aspects of biographical authority with relation to western women's subjectivities. And two chapters analyse the political and ethical implications of postmodernist/postcolonial theory on women's biographical speech. The study concludes that women's authority manifested in biographical speech is undoubtedly problematic but that feminist-inspired initiates continue to be productive.